A Semantic Study of Metaphorical Language in Modern Khmer Literature: The Case of Nou Hach’s Phka Sropoun - Samnang Pann; Sarom Mok (Journal of English Language Learning, 2026)
The main purposes of this study explore the conceptual metaphors within modern Khmer literature via the novel entitled “Phka Sropoun” and identify the types of metaphors utilized in modern literary through this novel. Employing a descriptive qualitative research design, data was systematically sampled and extracted from Nou Hach’s canonical novel entitled “Phka Sropoun”, a foundational text in the national 10th-grade Khmer literature curriculum of Ministry of Education Youth and Sport. The semantic analysis of the text identified 45 distinct figurative sentences containing 46 operational metaphorical instances. These instances were classified into 11 categories in Phka Sropoun, revealing a highly embodied and culturally grounded figurative system, respectively. The spatial metaphors constitute the dominant category, accounting for 34.78% (n = 16) of all occurrences. The structural metaphors and physiological metaphors each account for 13.07% (n = 6), grammaticalized and cultural or literary metaphors, each comprising 10.86% (n = 5), and the smaller presence of remaining categories—including technological and tactile each comprising 4.34% (n = 2), orientational, ontological, extended visual and kinetic metaphors, each comprising 2.17% (n = 1)—occur less frequently but contribute to the overall conceptual diversity of all identified expressions. The findings demonstrate that the stark hegemony of spatial metaphors within the novel entitled ``Phka Sropoun`` underscores that the novel's conceptual infrastructure is fundamentally dependent on physical and environmental dimensions to articulate abstract psychological states and narrative trajectories. Moreover, the substantial salience of physiological, structural, and cultural-literary schemas reveals a figurative matrix that is simultaneously rooted in universal embodied cognition and deeply inextricably bound to the specific socio-cultural landscape of Cambodia. Consequently, this study strongly recommends that future research scale the application of Conceptual Metaphor Theory (CMT) across a wider, diachronic corpus of 20th-century Khmer literature; such investigation is imperative to ascertain whether this rigorous reliance on spatial mapping represents an idiosyncratic stylistic signature of Nou Hach or signals a foundational, institutionalized cognitive paradigm across the modern Khmer literary tradition.